Health Risks of Mobile Phone Addiction Among College Students in China. - Mei, Songli; Hu, Yueyang; Wu, Xiaogang; Cao, Ruilin; Kong, Yixi; Zhang, Liwei; Lin, Xinli; liu, Qian; Hu, Yuanchao; Li, Li (International Journal of Mental Health & Addiction, 2023)
Mobile phone addiction (MPA) is a widespread problem in China, and college students face an especially high risk of its associated consequences. This study aimed to examine the interactions between level of mobile phone addiction and duration of mobile phone use and their impacts on psychological health, physical health, and sleep status of Chinese college students. Our study was a cross-sectional questionnaire-based survey which applied stratified random sampling method to recruit 946 participants. The level of mobile phone addiction was measured by Mobile Phone Addiction Index Scale. Sleep status was assessed by Pittsburg Sleep Quality Index. Designed questions were asked to evaluate the psychological and physical health status of the previous month of participants. The prevalence of MPA among Chinese undergraduates was estimated to be 36.6%. Severe MPA was significantly associated with psychological problems (anxiety symptoms, depressive symptoms, loneliness, social anxiety, impaired concentration, and sad or hopeless), physical problems (palpitation, nausea, and asphyxia), and sleep problems (sleep quality, sleep latency, sleep disturbances, sleep duration, and sleep dysfunctions). Interaction analysis indicated that college students with severe MPA who used their phones for more than 4 hours everyday were more likely to develop above problems. The findings reveal that relieving the MPA and controlling duration of phone use can ameliorate the psychological, physical, and sleep-related issues.